GEORGIA AFTER NOVEMBER 2003: ACHIEVEMENTS AND TRENDS - PICHKHADZE, Shalva (CENTRAL ASIA AND THE CAUCASUS, 2005)
There is a common opinion that the post-November 2003 events in Georgia should help to consolidate its statehood and state institutions. The most important of these events were: peacefully ridding Ajaria (and the whole country) of Aslan Abashidze, uniting several ministries into one, and reducing the army of bureaucrats. The new leaders of Georgia have also been paying more attention to its armed forces, and so the list can go on. Every revolution also has its negative aspects; in Georgia they left grim memories. Since the day of independence, power has changed three times through coups and bloodshed, but never according to the Constitution. Coups and bloodshed have become a habit—the constitution was no longer regarded as having value. The next coup was discussed as something trivial like making arrangements for spending an evening with friends or having a friendly game of cards. Coups relieved people of the need to think during election campaigns and of the opportunity to make a well-substantiated choice. Not infrequently, when talking among themselves in various backyards where the common people normally congregate, the Tbilisi populace consoled itself with, “We can always topple them if they turn out to be bad.” For my part I am prepared to accept a coup (or a revolution—tick the appropriate box) if it radically changes the situation for the better. The promises of the powers that be and them dreams are better left aside—it is the action that counts. Leaders are judged by their ability to cure the ills of the past and to capitalize on the positive factors. The fifteen months which have elapsed since the events of November 2003 are not enough to pass a final judgment yet are more than enough to size up the trends.